Phase equilibria and interfacial properties of two-dimensional Yukawa fluids - Méndez-Maldonado, G.A.; González-Melchor, M.; Alejandre, J. (Condensed Matter Physics, 2012)
Molecular dynamics simulations of two-dimensional soft Yukawa fluids are performed to analyze the effect that the range of interaction has on coexisting densities and line tension. The attractive one-component fluid and equimolar mixtures containing positive and negative particles are studied at different temperatures to locate the region where the vapor-solid and vapor-liquid phases are stable. When the range of interaction decreases, the critical temperature of the attractive one-component systems decreases. However, for the charged mixtures it increases, and this opposite behaviour is understood in terms of the repulsive interactions which are dominant for these systems. The stable phase diagram of two-dimensional fluids is defined for smaller values of the decay parameter λ than that of fluids in three dimensions. The two-dimensional attractive one-component fluid has stable liquid-vapor phase diagram for values of λ, in contrast to the three-dimensional case, where stability has been observed even for values of λ<15. The same trend is observed in equimolar mixtures of particles carrying opposite charges. Для того, щоб проаналiзувати, як впливає область взаємодiї на спiвiснуюючi густини i лiнiйний натяг, здiйснено симуляцiї методом молекулярної динамiки двовимiрних м’яких Юкава-плинiв. Притягальний однокомпонентний плин та еквiмолярнi сумiшi, що мiстять позитивнi i негативнi частинки, дослiджувалися при рiзних температурах таким чином, щоб визначити область, в якiй є стiйкими фази пара-тверде тiло i пара-рiдина. Зi зменшенням областi взаємодiї зменшується критична температура притягальних однокомпонентних систем. Проте для заряджених сумiшей вона зростає, i ця вiдмiннiсть у поведiнцi по-яснюється наявнiстю вiдштовхувальної взаємодiї, яка домiнує в цих системах. Дiаграма стiйкої фази двовимiрних плинiв є отримана для менших значень параметра затухання λ, нiж у випадку тривимiрних плинiв. Двовимiрний притягальний однокомпонентний плин має стiйку фазову дiаграму рiдина-пара для значень λ < 3, що вiдрiзняється вiд тривимiрного випадку, для якого стiйкiсть спостерiгається навiть для значень λ < 15. Така ж тенденцiя спостерiгається в еквiмолярних сумiшах протилежно заряджених частинок.